229k views
5 votes
Simplify the expression 5-2y + (-8y) +6.8


User Capotej
by
4.8k points

2 Answers

3 votes

answer:

5-2y + (-8y) + 6.8

simplified:

11.8-10y

User Jslefche
by
4.6k points
4 votes

Explanation:

Let's simplify step-by-step.

5−2y−8y+6.8

=5+−2y+−8y+6.8

Combine Like Terms:

=5+−2y+−8y+6.8

=(−2y+−8y)+(5+6.8)

=−10y+11.8

Description:

The first step is to simplify the first equation that is 5−2y−8y+6.8 . After that your answer will lead up to 5+−2y+−8y+6.8 . Then the last step is to Combine like terms. At the end your answer will lead up to −10y+11.8.

So 5-2y + (-8y) +6.8 = −10y+11.8

Answer: −10y+11.8

Hope this helps.

User Biboozz
by
5.3k points